2014
DOI: 10.1520/jte20130157
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Consistency of Asphalt Density Measurement Methods Over a Wide Range of Air Voids

Abstract: The overall purpose of this paper is to identify the most reliable bulk mixture specific gravity (Gmb) measurement method for dense graded asphalt concrete that can be used for a wide range of air voids and specimen types. A secondary purpose is to identify ranges of conditions where less established Gmb measurement methods are suitable. A comprehensive literature review was performed to identify promising density test methods for further study. Findings from studies comparing AASHTO T166 (saturated surface dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Cross (8,9), who researched CIR, and NCHRP Synthesis 421 (21), on in-place recycling, expressed concerns that T 166 may not be suitable because of water absorption issues caused by typically high air voids in recycling mixtures. The CIR V a levels found in the literature are often higher than the 8% to 9% value mentioned by Howard and Doyle (7). The literature reports V a levels of 2% to 14% (17), 8.9% to 14.4% (18), 13.7% to 16.4% (20), 6% to 10% (11, 13), 9.7% to 14.2% (8), 8% to 17% (12), 9.2% to 17.9% ( 14), 5.8% to 10% ( 16), and 6.3% to 22.4% (6).…”
Section: Bulk Specific Gravity Of Cirmentioning
confidence: 55%
See 2 more Smart Citations
“…Cross (8,9), who researched CIR, and NCHRP Synthesis 421 (21), on in-place recycling, expressed concerns that T 166 may not be suitable because of water absorption issues caused by typically high air voids in recycling mixtures. The CIR V a levels found in the literature are often higher than the 8% to 9% value mentioned by Howard and Doyle (7). The literature reports V a levels of 2% to 14% (17), 8.9% to 14.4% (18), 13.7% to 16.4% (20), 6% to 10% (11, 13), 9.7% to 14.2% (8), 8% to 17% (12), 9.2% to 17.9% ( 14), 5.8% to 10% ( 16), and 6.3% to 22.4% (6).…”
Section: Bulk Specific Gravity Of Cirmentioning
confidence: 55%
“…Figure 4a shows that, on average, T 269 air voids were 1.1% greater than those of T 331. Howard and Doyle found that V a(T269) minus V a(T331) ranged from 0.9% to 2.6% for air voids of 4% to 10% (7). CIR V a(T269) minus V a(T331) was on the lower end of this range despite air voids ranging from approximately 18% to 28%.…”
Section: Cir G Mb Test Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Multiple investigations have recently considered changes from SSD measurement to vacuum sealing methods (14)(15)(16). Howard and Doyle considered about 2,400 data points to conclude that AASHTO T 331 was the most accurate and versatile method to measure G mb over a wide range of mixtures (14).…”
Section: History Of In-place Density Measurementmentioning
confidence: 99%
“…Multiple investigations have recently considered changes from SSD measurement to vacuum sealing methods (14)(15)(16). Howard and Doyle considered about 2,400 data points to conclude that AASHTO T 331 was the most accurate and versatile method to measure G mb over a wide range of mixtures (14). Buchanan tested G mb on four mix types (open-graded friction course, stone mastic asphalt, coarse Superpave ® , and fine Superpave) with four density measurement protocols (i.e., SSD, dimensional, parafilm, and vacuum sealing) (15).…”
Section: History Of In-place Density Measurementmentioning
confidence: 99%